Rezension von: Brücker, Christian Ludwig; Loderer, Klaus J., Backnanger Stadtchronik - Fritz, Gerhard (Backnanger Jahrbuch, 1992)
Christian Ludwig Brücker und Klaus Loderer: Backnanger Stadtchronik. Herausgegeben von der Stadt Backnang, Stadtarchiv. Backnang: Michel 1988, 260 S.